“SLUZHBOVTSI” (OFFICIALS) IN THE 1920-30’s UKRAINIAN LITERARY TRANSLATIONS (based on the abridged and free translations by E. Zbars’ka) - Vasylyeva, N. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article pioneers introduction of the noun “sluzhba” (job, service) and its derivative “sluzhbovets’” (an official) into the free and abridged translations by E.Zbars’ka of James Oliver Curwood’s works “Kazan” and “Baree, son of Kazan”. The noun “sluzhba” is introduced into the translation by means of paraphrase, its derivative “sluzhbovets’” is introduced into the translation by means of translation transformation of concretization. The introduction of the noun “sluzhba” into the translations by E.Zbars’ka of James Oliver Curwood’s works could be caused by some peculiarities of E.Zbars’ka individual translating style. Also it could be caused by the then tendency for the domestication of translations, which, in its turn, might be caused by the then so called “iron curtain”. The usage of the noun “sluzhba” and the derivatives in the works of the then translated literature (free and abridged translations by E.Zbars’ka) is being compared to the usage of the noun “sluzhba” and its derivatives in the works of the then national literature (the works of Valeriyan Pidmohylnyi, Mike Yohansen and Mikhail Zoshchenko). An attempt is being made to explain the introduction of the noun “sluzhbovets’” into E.Zbars’ka’s translation by the then professional and social composition of the population in the country of the source language. Also an attempt is being made to explain the usage of the noun “sluzhba” and its derivatives in the works of the then translated literature as well as in the works of the then national literature from the point of view of literary polysystem theory by Itamar Even-Zohar. Prospects for research are to continue the study of the 1920-30’s Ukrainian translation heritage, namely the study of Ukrainian literary free and abridged translations of the 1920-30’s, the study of their similarities and of their connection with the then Ukrainian national literature. _______________ References • 1. Even-Zohar, Itamar Mistse perekladnoyi literatury v literaturniy polisystemi. Translated by Andriy Savenets’. [The position of translated literature within the literary polysystem]. Available at: http://www.tau.ac.il/ itamarez/works/papers/translated/iez-misce-pl.pdf • Kalnychenko O.A. Poliakova Yu.Yu. Ukrayins’ka perekladoznavcha dumka 1920-kh – pochatku 30-kh rokiv [Ukrainian translation studies thought of the 1920’s and of the beginning of 1930’s. Edited by Leonid Chernovatyi and Vyacheslav Karaban] – Vinnytsya, «Nova Knyha» Publ., 2011. 504p. • 3. Kolomiyets L.V. Ukrayins’kyi khudozhniy pereklad ta perekladachi 1920-30-kh rokiv [Ukrainian Literary Translation and Translators of the 1920-30’s]. Kyivs’kyi universytet Publ., 2013, 559p. • Russian-Ukrainian Academic dictionary by A.Kryms’kyi and S.Yefremov. Available at: r2u@org.ua • Sedlerova A.I. Movnyi ta pozamovnyi kontekst perekladats’koho dorobku V.Pidmohyl’noho (na materiali perekladiv z frantsuz’koyi movy) [Lingual and extralingual context of Valer’yan Pidmohyl’nyi’s translation heritage (based on the translations from French language). • Tsymbal Yaryna. The works of Mike Johansen in the context of Ukrainian avant-garde of the 1920-30’s. Ph.D. phyl. sci.diss.. Kyiv, 2003. (In Ukr.) • Zhytkov B.S. Rasskazy o zhyvotnykh. [Stories about animals]. Smolensk, Rusich Publ.,2007 – 64p. • Zoshchenko Mikhail. Sobraniye sochineniy v triokh tomakh. [Collected Works in three volumes]. Tom 2 [Volume2], Golubaya kniga (rasskazy, komediyi) [The blue book: Stories, Comedies] Moscow.: AST: Zebra E publishers, 2010. 384p. • Yohansen, Mike, Pryhody Mak-Leistona, Harry Ruperta ta inshykh. [Adventures of Mac- Leiston, Harry Ruppert and others]. Mike Yohansen, Selected works. Kyiv, Smoloskyp publ. 2009, 768p. • Kervud Dzh. O. Kazan. Kharkiv, Derzhavne vydavnytstvo Ukrainy Publ., 1928. 108p. (Engl. ed.: James Oliver Curwood. Kazan) • Kervud Dzh. O. Kazaniv syn. Kharkiv, Kyiv, Molodyi Bil’shovyk Publishers, 1934. 143 p. (Engl. ed.: James Oliver Curwood. Baree, Son of Kazan) • Kervud Dzh. O. Vovk Kazan – viddanyi drug. Kyiv, Znannya Publ. 2015. – 190p. (Engl. ed. James Oliver Curwood. Kazan. • Curwood James Oliver. Korol’ gryzli [Engl. The Grizzly King] Vydavnytstvo Staroho Leva publ. 2016, 236 p. • Pidmohylnyi V.P. Misto [The City] // Opovidannya. Povist’. Romany. [Stories. Tale,.Novels] Kyiv, Naukova dumka Publ., 1991. 800 p. • Pidmohylnyi Valeryan. Ostap Shaptala // Tretya revolyutsia: Opovidannya, povisti, roman.[The third Revolution: Stories, tales, novel]. Kyiv, Ukr. pys’mennyk Publ. 2012. 619p. • Pidmohylnyi V. Nevelychka drama [A little touch of Drama] Kyiv, Znannia Publ., 2014. 294p. • Seton-Tompson, E. Malen’ki dykuny. Derzhavne vydavnytstvo Ukrainy Publ., 1929. 120p. (Engl. ed.: Thompson Seton, Ernest. Two little savages • Seton-Tompson, E. Dva malen’kyh dykuny. Kyiv, Znannya Publ. 2017. – 367 p. (Engl. ed.: Thompson Seton, Ernest. Two little savages) • James Oliver Curwood. Kazan. Available at: http://www.ebooksread.com/authors-eng/james-oliver-curwood/kazan-8-4.shtml • James Oliver Curwood. Baree, son of Kazan. Available at: http://www.ebooksread.com/authors-eng/james-oliver-curwood/baree-son-of-kazan-01e.shtml • Thompson Seton, Ernest. Two Little Savages. Available at: http://www.gutenberg.net/dirs/1/3/4/9/13499/13499-h/13499-h.htm